Purification and conversion of Malaysian iron ores into industrial grade iron oxide colour pigment - Wong, Y.W.; Woon, H.S.; Tan, C.Y. (Maney Publishing, 2014)
This work proposes a method of converting local iron ores into colour pigments to add commercial and technical values to the commodity. Iron ores were subjected to hammer-crushing and two milling techniques (low-energy ball milling and high-energy milling) to produce submicron or ultrafine pigment particles. Effects of different milling duration, speed and charge type on the particle size were investigated. X-ray diffraction and energy-dispersive X-ray spectroscopy scans revealed that the ores contain hematite and goethite phases, with 54% of Fe and 35.38% of O. Particle size analysis showed that high-energy milling (14 hours, 11 mm charge, 550 rev min(-1)) was effective in producing particles as small as 1.379 mu m. Commision Internationale de l'Eclairage L* a* b* colour values measured were L* of 49.7, a* of 21.2 and b* of 15.8.